C1.1 Development and implementation of congenital hyperinsulinism transition clinic pathway. (4th October 2017) - Poisson, J; Pitfield, C; Gilbert, C; Morgan, K; Cunjamalay, A; Misra, S; Oliver, N; Shah, P
Abstract : Background: Congenital Hyperinsulinism (CHI) is caused by inappropriate secretion of insulin which leads to severe hypoglycaemia in infants and children causing hypoglycaemic brain injury if not managed promptly. There is no designated centre in the country providing highly specialised expert input in adults with Hyperinsulinism. It was recognised that some young people at GOSH were discharged to local adult endocrinologist/diabetologist with little or no CHI experience and no multidisciplinary team input and support. The aim of our project was to develop and implement CHI transition clinics and resources to support patients, parents/carers and healthcare professionals. Methods: The patients that are older and imminently needed transitioning were seen in the clinic first. A joint multi-disciplinary CHI transition clinic takes place for 13–20 years old patients. The clinic takes place once a month at the Royal London Homeopathic Hospital on Friday afternoons. The clinic would have multi-disciplinary team this includes paediatric and adult endocrinologist, psychologist, clinical nurse specialists and dietitian. Information on pre and post clinic outcome and PedsQL were collected during the clinic appointment. Results: Over 6 months, we held 6 transition clinics, with 25 patients seen. Qualitative and Quantitative data has been collected and patient feedback is very positive. Resources for patients and healthcare professionals have been created to support the transition process. Conclusion: Transition from paediatric to adult care is a very import part of the patient journey. Transition needs to be planned and structured to meet the needs of individual patients and should include a multi-disciplinary team. Caring for the mental and social wellbeing of the patient is just as important as their clinical needs. Patients and parents have found the transition clinic to be very useful. We will use the qualitative data collected to continually improve the patient experience and build our resource toolkit.